Asphalt-based silicon carbon negative electrode material, preparation method and application thereof

CN118619252BActive Publication Date: 2026-10-20INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410739043.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2026-10-20
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

[0005]针对目前硅基负极中硅体积膨胀导致的容量损失,硅导电性差的问题,本发明提供了一种沥青基硅炭负极材料及制备方法和应用

Benefits of technology

本发明提出的一种高强度炭涂层,来源于煤沥青中的提取物,涂覆较少的炭即可实现对硅体积膨胀的有效抑制;以沥青作为粘接剂并辅以球磨技术,将硅@炭均匀锚定在石墨表面,外层涂覆沥青。此种结构避免了纳米硅@炭的团聚,同时石墨作为导电网络可弥补硅导电性差的弊端,双包覆层进一步限制硅体积膨胀。所制备的硅炭复合物作为负极材料,显著提高了锂离子电池的首次库伦效率、倍率性能以及循环稳定性。本发明公开的硅炭负极材料的制备方法,步骤简单,所使用到的原料成本低廉,易实现工业化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619252B_ABST
    Figure CN118619252B_ABST
Patent Text Reader

Abstract

The application discloses a pitch-based silicon-carbon negative electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion battery negative electrode materials. In view of the capacity loss caused by the volume expansion of silicon in the current silicon-based negative electrode and the poor conductivity of silicon, the pitch component is cut by using an organic solvent; the agglomeration of nano-silicon particles in the viscous pitch solution is inhibited through ultrasonic dispersion; the nano-silicon particles uniformly coated with pitch are obtained through mechanical stirring; carbonization treatment is then carried out; graphite is mixed with pitch, ball-milled, then added into the aforementioned product for continuous ball-milling, and carbonization treatment is carried out; and finally, pitch-based silicon-carbon negative electrode material is obtained through pitch coating. The pitch-based silicon-carbon negative electrode material adopts coal pitch as a carbon source, obtains a firm carbon coating through a simple pitch component separation process, and further optimizes the structure of the silicon-carbon and graphite composite material, thereby significantly inhibiting the volume expansion of silicon. The pitch-based silicon-carbon negative electrode material exhibits excellent cycle stability as a lithium battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of lithium-ion battery anode materials, specifically relating to an asphalt-based silicon-carbon anode material, its preparation method, and its application. Background Technology

[0002] In recent years, the demand for lithium-ion batteries has continued to surge, and they have been widely used in new energy vehicles, portable electronic devices, and other fields. This widespread market application has placed higher demands on lithium batteries, especially on lifespan and safety performance. This requires lithium batteries to have higher energy density and better cycle performance. However, the currently used traditional anode material—graphite—has a theoretical specific capacity of only 372 mAh / g. Even though current achievable levels are very close to this theoretical value, it is still difficult to meet market requirements. Based on the demand for higher energy density, it is necessary to explore anode materials with superior performance, such as silicon. Silicon has a theoretical specific capacity of 4200 mAh / g, which is currently the highest known theoretical specific capacity for an anode material. Furthermore, silicon has advantages such as low operating voltage (0.4 V) and abundant reserves. Therefore, silicon is considered the next-generation anode material for lithium-ion batteries.

[0003] Silicon offers many advantages as an anode material, but it also presents several challenges. Firstly, silicon has very low electrical conductivity, leading to poor electrochemical reaction kinetics. Another drawback is the significant volume expansion after lithium intercalation, causing silicon particles to pulverize and crack, and forming an unstable solid electrolyte interphase, ultimately resulting in battery capacity decay. Currently, a relatively effective and commonly used method for modifying silicon-based anodes is to composite them with carbon materials to prepare carbon-doped silicon or carbon-coated silicon composites. Therefore, the mechanical strength of the carbon coating is crucial, as it determines whether it can effectively suppress silicon volume expansion without cracking. Chinese patent (CN114906834A) discloses a method for preparing pitch-based silicon-carbon anode materials. This patented technology achieves uniform dispersion of nano-silicon materials and overall cycle stability by mixing graphene, pitch, and silicon powder. However, the graphene used to prepare this material is relatively expensive, and the initial capacity is low, less than 350 mAh g⁻¹. -1 Chinese patent CN113363458A discloses a method for preparing silicon-carbon anode materials. This patented technology reduces the volume expansion of silicon during cycling by coating the surface of nano-silicon with graphite. However, the protective effect of graphite in this preparation method is very limited; silicon still comes into direct contact with the electrolyte, and side reactions still occur repeatedly without avoidance. After only 80 cycles, the capacity drops to less than 90% of the initial capacity, indicating poor long-term cycling performance.

[0004] Therefore, on the one hand, it is still necessary to synthesize a carbon coating with sufficiently high strength to ensure that it can still play a protective role after silicon lithium intercalation expansion. On the other hand, it is necessary to rationally optimize the structure of silicon-based composite materials to ensure that nanoscale silicon particles are uniformly dispersed in the carbon material as much as possible. The prepared silicon-based composite material should not only meet the cycle performance requirements of lithium-ion batteries, but also take into account capacity, initial coulombic efficiency, and rate performance. Summary of the Invention

[0005] To address the issues of capacity loss and poor conductivity caused by silicon volume expansion in current silicon-based anodes, this invention provides a pitch-based silicon-carbon anode material, its preparation method, and its application.

[0006] One of the objectives of this invention is to provide a high-strength carbon coating suitable for coating on silicon surfaces or for use in silicon-carbon composites.

[0007] The second objective of this invention is to provide a method for preparing silicon-carbon-graphite composite materials that is simple to operate, low in cost, and easy to industrialize.

[0008] To achieve the above objectives, the present invention employs the following technical solutions: A method for preparing a pitch-based silicon-carbon anode material includes the following steps: Step 1: Dissolve coal tar pitch in an organic solvent by high-speed stirring, centrifuge, collect the supernatant, heat the supernatant in an oil bath, and recover the evaporated solvent through a condenser to obtain the asphalt-containing component A, which is then vacuum dried for later use. Step 2: Dissolve the asphalt-containing component A material dried in Step 1 in tetrahydrofuran solvent and stir magnetically until fully dissolved. Then add nano-silica powder and disperse ultrasonically. Stir magnetically to obtain a silicon@asphalt composite solution. Heat in a water bath until the tetrahydrofuran is completely evaporated to obtain the silicon@asphalt composite. Dry under vacuum for later use. Step 3: Carbonize the silicon@asphalt composite at high temperature to obtain silicon@carbon; Step 4: Add a mixture of graphite and coal tar pitch to silicon@carbon and ball mill it, then carbonize it to obtain an intermediate product; Step 5: Dissolve coal tar pitch in tetrahydrofuran solution until fully dissolved, then add intermediate product and stir magnetically. Then heat and stir in a water bath until the solution is completely evaporated. Dry the product under vacuum and then carbonize it at high temperature to obtain silicon@carbon-graphite composite, which is pitch-based silicon-carbon anode material.

[0009] Furthermore, the high-speed stirring in step 1 can be magnetic stirring.

[0010] Furthermore, the organic solvent in step 1 is one or a combination of toluene, N,N-dimethylacetamide (DMA), or N-methylpyrrolidone (NMP).

[0011] Furthermore, the coal tar pitch in steps 1, 4, and 5 refers to one or more combinations of low-temperature coal tar pitch with a softening point between 35℃ and 120℃, medium-temperature coal tar pitch with a softening point between 75℃ and 95℃, high-temperature coal tar pitch with a softening point between 95℃ and 120℃, and mesophase pitch.

[0012] Furthermore, the oil bath heating temperature in step 1 is 110℃~200℃; the vacuum drying temperature in steps 1, 2 and 5 is 65℃~120℃, and the drying time is 2h~12h.

[0013] Furthermore, in step 2, the mass ratio of asphalt to tetrahydrofuran solvent is 1:200-500, and the mass ratio of asphalt to nano-silica powder is 1:0.1-10; the average molecular weight of the asphalt-containing component A in step 2 is 240 g / mol-630 g / mol; and the nano-silica powder in step 2 is crystalline silicon with a particle size of 20 nm-150 nm.

[0014] Furthermore, in step 3, the carbonization temperature is 700℃~1100℃, held at a constant temperature for 2h~4h, and the heating rate is 1℃ / min~5℃ / min; in step 4, the carbonization temperature is 350℃~550℃, the heating rate is 1℃ / min~5℃ / min, and held at a constant temperature for 1h~3h; in step 5, the carbonization temperature is 700℃~1100℃, held at a constant temperature for 2h~4h, and the heating rate is 1℃ / min~5℃ / min; the inert gas used in the carbonization of steps 3, 4 and 5 is one of nitrogen, argon and helium.

[0015] Further, in step 4, a mixture of graphite and coal tar pitch is added to silicon@carbon and ball-milled. The volume ratio of the mixture to the milling beads is 1:1 to 5, the milling speed is 300 rpm / min to 600 rpm / min, and the milling time is 1 h to 10 h. The graphite in step 4 is either artificial graphite or natural graphite, and the particle size of the graphite is 2 μm to 20 μm. The mass ratio of graphite to coal tar pitch in step 4 is 1:0.1 to 0.3, and the mass ratio of graphite and coal tar pitch to silicon@carbon is 1:0.05 to 0.25.

[0016] Furthermore, in steps 2 and 5, the magnetic stirring time is 3h to 24h, the rotation speed is 300 rpm / min to 500 rpm / min, the water bath heating temperature is 60℃ to 75℃, and the water bath heating and stirring time is 0.5h to 2h.

[0017] The application of a pitch-containing component A material obtained in a method for preparing pitch-based silicon-carbon anode material as a coating on a silicon surface.

[0018] Application of Pitch-Based Silicon-Carbon Anode Material Prepared by a Method for Preparing Pitch-Based Silicon-Carbon Anode Material in Batteries Compared with the prior art, the present invention has the following advantages: This invention proposes a high-strength carbon coating derived from coal tar pitch. A relatively small amount of carbon is required to effectively suppress silicon volume expansion. Using pitch as a binder and ball milling, silicon@carbon is uniformly anchored onto a graphite surface, with an outer layer of pitch coating. This structure avoids the agglomeration of nano-silicon@carbon, while graphite, acting as a conductive network, compensates for the poor conductivity of silicon. The double coating further restricts silicon volume expansion. The prepared silicon-carbon composite, as an anode material, significantly improves the initial coulombic efficiency, rate performance, and cycle stability of lithium-ion batteries. The preparation method of the silicon-carbon anode material disclosed in this invention is simple, uses inexpensive raw materials, and is easily industrialized. Attached Figure Description

[0019] Figure 1 This is a flowchart illustrating the preparation of the silicon-carbon composite according to the present invention.

[0020] Figure 2 This is a schematic diagram of the pitch-based silicon-carbon anode material provided in Embodiment 1 of the present invention.

[0021] Figure 3 The image shows the microstructure of silicon@carbon provided in Embodiment 1 of the present invention.

[0022] Figure 4 This is a microscopic morphology diagram of the silicon-carbon composite (i.e., silicon@carbon-graphite) provided in Example 1 of the present invention.

[0023] Figure 5 The first charge-discharge curve and coulombic efficiency of the lithium battery prepared using the silicon-carbon composite provided in Example 1 of this invention are shown.

[0024] Figure 6 Cyclic test results of a lithium battery prepared using the silicon-carbon composite provided in Example 1 of this invention. Detailed Implementation

[0025] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.

[0026] The coal tar pitch used in this invention refers to low-temperature coal tar pitch with a softening point between 35℃ and 120℃, medium-temperature coal tar pitch with a softening point between 75℃ and 95℃, high-temperature coal tar pitch with a softening point between 95℃ and 120℃, and one or more combinations of mesophase pitch.

[0027] The organic solvent used is one or a combination of toluene, N,N-dimethylacetamide (DMA), and N-methylpyrrolidone (NMP). The graphite used is either artificial graphite or natural graphite. The inert gas used in carbonization is one of nitrogen, argon, and helium. The nano-silicon powder is crystalline silicon.

[0028] This invention provides a method for preparing silicon-carbon composite anode materials, such as... Figure 1 As shown, it includes the following steps: Step 1: Dissolve coal tar pitch in an organic solvent by high-speed stirring, centrifuge, collect the supernatant, heat the supernatant in an oil bath at 110℃~200℃, and recover the evaporated solvent through a condenser to obtain a pitch-containing component A substance with an average molecular weight of 240 g / mol~630 g / mol. Vacuum dry the component for 2 h~12 h at a temperature of 65℃~120℃ for later use. Step 2: Dissolve the asphalt-containing component A material dried in Step 1 in tetrahydrofuran solvent and stir magnetically until fully dissolved. Then add nano-silicon powder (crystalline silicon with a particle size of 20 nm to 150 nm) and disperse ultrasonically. Then stir magnetically to obtain a silicon@asphalt composite solution. Heat in a water bath until the tetrahydrofuran is completely evaporated to obtain the silicon@asphalt composite. Vacuum dry at a temperature of 65℃ to 120℃ for 2 h to 12 h for later use. The mass ratio of asphalt to tetrahydrofuran solvent is 1:200-500, and the mass ratio of asphalt to nano-silica powder is 1:0.1-10. Step 3: Under an inert gas atmosphere, the temperature is increased from room temperature to 700℃~1100℃ at a heating rate of 1~5℃ / min to carbonize the silicon@asphalt composite at high temperature for 2~4 h to obtain silicon@carbon. Step 4: Add a mixture of graphite (particle size 2~20μm) and coal tar pitch to silicon@carbon and ball mill (volume ratio of mixture to milling beads 1:1~5) (milling speed 300~600 rpm / min, milling time 1~10 h). Then, under an inert gas atmosphere, raise the temperature from room temperature to 350℃~550℃ at a heating rate of 1~5℃ / min and carbonize and sinter for 1 h to obtain an intermediate product. In step 4, the mass ratio of graphite to coal tar pitch is 1:0.1~0.3; the mass ratio of graphite and coal tar pitch to silicon@carbon is 1:0.05~0.25.

[0029] Step 5: Dissolve coal tar pitch in tetrahydrofuran solution until fully dissolved, then add intermediate product and magnetically stir at 300-500 rpm / min for 3-24 hours. Then heat in a water bath at 60℃-75℃ for 0.5-2 hours and stir until the solution is completely evaporated. Vacuum dry the product at 65℃-120℃ for 2-12 hours. Then, under an inert gas atmosphere, heat the temperature from room temperature to 700℃-1100℃ at a heating rate of 1-5℃ / min and carbonize at high temperature for 2-4 hours to obtain silicon@carbon-graphite composite, which is pitch-based silicon-carbon anode material.

[0030] Example 1

[0031] Step 1: Add 5 g of medium-temperature coal tar pitch to 75 mL of toluene, place it on a magnetic stirrer and stir to dissolve at 350 rpm / min and 30℃ for 1.5 h. Centrifuge the above pitch solution at 9500 rpm / min for 10 min. Take the supernatant and label it as pitch-toluene solution. Retain the centrifugation insoluble matter and dry it in a vacuum oven at 120℃ for 12 h. Heat the above pitch-toluene solution in an oil bath at 111℃, recover the evaporated solvent through a condenser, and recover the pitch-toluene soluble matter (TS), which is then dried in a vacuum oven at 120℃ for 12 h. Step 2: Take 0.1 g TS, add 50 mL tetrahydrofuran, place on a magnetic stir bar and stir at 300 rpm. -1 The mixture was stirred at a certain speed for 30 min to obtain a TS-tetrahydrofuran solution. 0.6 g of 50 nm diameter silicon nanoparticles were added to the TS-tetrahydrofuran solution and ultrasonically dispersed for 30 min to ensure uniform dispersion of the silicon nanoparticles and prevent agglomeration. The silicon-TS-tetrahydrofuran suspension was then stirred on a magnetic stirrer for 24 h at 400 rpm / min to obtain a silicon@TS composite solution. The silicon@TS composite solution was then placed in a water bath at 68 °C and stirred until the tetrahydrofuran was completely evaporated at 300 rpm / min. The resulting silicon@TS composite was then dried in a vacuum oven at 80 °C for 2 h.

[0032] Step 3: The dried Si@TS precursor was placed in a tube furnace under an argon atmosphere for high-temperature sintering. The carbonization conditions were: heating from room temperature to 700℃ and holding at this temperature for 2 hours, with a heating rate of 2℃ / min. -1 There is no intermediate stop. After carbonization, the product silicon@carbon is obtained.

[0033] Step 4: Mix 0.3 g of medium-temperature coal tar pitch and 1.7 g of artificial graphite in a ball mill jar and ball mill for 5 hours at a speed of 400 rpm / min. Take 0.2 g of Si@C from Step 3 and mix it with 2 g of pitch-coated graphite. Add three times the volume of the material to the ball milling beads and ball mill for 1 hour at a speed of 400 rpm / min. Place the ball-milled product in a tube furnace under an argon atmosphere for sintering. The carbonization conditions are: heating from room temperature to 450°C and holding at this temperature for 1 hour, with a heating rate of 2°C / min. -1 There was no stop in between.

[0034] Step 5: Add 0.2 g of medium-temperature coal tar pitch to 50 mL of tetrahydrofuran and stir on a magnetic stirrer at 300 rpm / min for 30 min to dissolve. Add 2 g of the ball-milled product and continue magnetic stirring for 3 h at 400 rpm / min. Place the solution in a water bath at 68°C and stir until the tetrahydrofuran is completely evaporated at 300 rpm / min. Place the intermediate product in a vacuum oven and dry at 80°C for 2 h. Place the dried product in a tube furnace and heat it from room temperature to 700°C under an argon atmosphere, holding it at this temperature for 2 h at a heating rate of 1°C / min without pause. After carbonization, the final product silicon@carbon-graphite is obtained.

[0035] Example 2

[0036] The method for preparing silicon-carbon composite anode material according to Example 1 differs in that: in step 1, 2.5 g of toluene-insoluble coal tar pitch at medium temperature is added to 36 mL of DMA, and stirred on a magnetic stirrer at 350 rpm / min and 30°C for 1 h. The mixture is then heated in an oil bath at 165°C.

[0037] Example 3

[0038] The method for preparing silicon-carbon composite anode material according to Example 1 differs in that: in step 1, 1.3 g of medium-temperature coal tar pitch DMA insolubles are added to 39 mL of NMP, and the mixture is stirred on a magnetic stirrer at 500 rpm / min and 30°C for 2.5 h. The mixture is then heated in an oil bath at 200°C.

[0039] Example 4

[0040] The method for preparing silicon-carbon composite anode material according to Example 1 differs in that: in step 4, 0.5 g of medium-temperature coal tar pitch and 1.5 g of artificial graphite are mixed and placed in a ball mill jar. 0.3 g of Si@C from step 3 is mixed with 2 g of pitch-coated graphite. In step 5, the carbonization temperature is 900℃, and the heating rate is 2℃ / min.

[0041] Example 5

[0042] The method for preparing silicon-carbon composite anode material according to Example 1 differs in that: in step 4, 0.5 g of silicon@carbon from step 3 is mixed with 2 g of pitch-coated graphite. Alternatively, 0.5 g of Si@C from step 3 is mixed with 2 g of pitch-coated graphite. In step 5, the carbonization temperature is 1100℃, and the heating rate is 5℃ / min.

[0043] Performance Testing: The silicon-carbon anode material obtained in Example 1 was used to prepare a lithium-ion battery anode sheet. Specifically, Si@C material, Super-P, CMC, and SBR were mixed and ground in a mass ratio of 80:10:5:5 and coated onto copper foil. After drying in a vacuum oven, it was cut into 1 cm diameter discs using a cutting machine. Half-cell assembly was completed in a glove box, using lithium metal foil as the counter electrode to assemble a 2032 type half-cell. The specific testing procedure was as follows: first, activation was performed once at a current density of 0.05 A / g, followed by cyclic testing at a current density of 0.5 A / g. The charging cutoff voltage was 1.5 V, and the discharging cutoff voltage was 0.01 V. The initial charge / discharge results are as follows. Figure 5 As shown, the discharge specific capacity is as high as 810 mAh / g, and the initial coulombic efficiency is approximately 85.3%. Test results are as follows... Figure 6 As shown, after 500 cycles, the capacity remained around 678 mAh / g, and the coulombic efficiency remained above 99.9% during the test. This excellent electrochemical performance indicates that the carbon coating obtained through the asphalt component separation process is very robust, and the further optimization of the silicon-carbon and graphite composite material structure significantly suppressed the volume expansion of silicon, resulting in a stable battery anode material structure.

[0044] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.

Claims

1. A method for preparing a pitch-based silicon-carbon anode material, characterized in that, Includes the following steps: Step 1: Dissolve coal tar pitch in an organic solvent by high-speed stirring, centrifuge, collect the supernatant, heat the supernatant in an oil bath, and recover the evaporated solvent through a condenser to obtain the asphalt-containing component A, which is then vacuum dried for later use; the average molecular weight of the asphalt-containing component A is 240 g / mol to 630 g / mol. Step 2: Dissolve the asphalt-containing component A from Step 1 in tetrahydrofuran solvent and stir magnetically until fully dissolved. Then add nano-silica powder and disperse ultrasonically, followed by magnetic stirring to obtain a silicon@asphalt composite solution. Heat in a water bath until the tetrahydrofuran is completely evaporated to obtain the silicon@asphalt composite, which is then vacuum dried for later use. The nano-silica powder in Step 2 is crystalline silicon with a particle size of 20 nm to 150 nm. The mass ratio of asphalt to tetrahydrofuran solvent in Step 2 is 1:200 to 500, and the mass ratio of asphalt to nano-silica powder is 1:0.1 to 10. Step 3: Carbonize the silicon@asphalt composite at high temperature to obtain silicon@carbon; the carbonization temperature in step 3 is 700℃~1100℃, and the temperature is held for 2h~4h, with a heating rate of 1℃ / min~5℃ / min. Step 4 involves ball milling a mixture of graphite and coal tar pitch into silicon@carbon, followed by carbonization to obtain an intermediate product. In step 4, the volume ratio of the mixture to the milling balls is 1:1 to 5, the milling speed is 300 rpm / min to 600 rpm / min, and the milling time is 1 h to 10 h. The graphite in step 4 is either artificial graphite or natural graphite, with a particle size of 2 μm to 20 μm. The mass ratio of graphite to coal tar pitch in step 4 is 1:0.1 to 0.3, and the mass ratio of graphite and coal tar pitch to silicon@carbon is 1:0.05 to 0.

25. Step 5: Dissolve coal tar pitch in tetrahydrofuran solution until fully dissolved, then add intermediate product and stir magnetically. Then heat and stir in a water bath until the solution is completely evaporated. Vacuum dry the product and then carbonize it at high temperature to obtain silicon@carbon-graphite composite, which is pitch-based silicon-carbon anode material. In step 5, the carbonization temperature is 700℃~1100℃, the temperature is held for 2 h~4 h, and the heating rate is 1℃ / min~5℃ / min.

2. The method for preparing a pitch-based silicon-carbon anode material according to claim 1, characterized in that: The organic solvent in step 1 is one or a combination of toluene, N,N-dimethylacetamide, or N-methylpyrrolidone.

3. The method for preparing a pitch-based silicon-carbon anode material according to claim 1, characterized in that: The coal tar pitch in steps 1, 4, and 5 refers to one or more combinations of low-temperature coal tar pitch with a softening point between 35℃ and 120℃, medium-temperature coal tar pitch with a softening point between 75℃ and 95℃, high-temperature coal tar pitch with a softening point between 95℃ and 120℃, and mesophase pitch.

4. The method for preparing a pitch-based silicon-carbon anode material according to claim 1, characterized in that: The oil bath heating temperature in step 1 is 110℃~200℃; the vacuum drying temperature in steps 1, 2 and 5 is 65℃~120℃, and the drying time is 2h~12h.

5. The method for preparing a pitch-based silicon-carbon anode material according to claim 1, characterized in that: The carbonization temperature in step 4 is 350℃~550℃; the inert gas used in the carbonization of steps 3, 4 and 5 is one of nitrogen, argon and helium.

6. The method for preparing a pitch-based silicon-carbon anode material according to claim 1, characterized in that: In steps 2 and 5, the magnetic stirring time is 3h to 24h, the rotation speed is 300 rpm / min to 500 rpm / min, the water bath heating temperature is 60℃ to 75℃, and the water bath heating and stirring time is 0.5h to 2h.

7. The application of the asphalt-containing component A material obtained in the preparation method of the asphalt-based silicon-carbon anode material according to claim 1 as a coating on the silicon surface.

8. The application of the pitch-based silicon-carbon anode material prepared by the method of any one of claims 1 to 6 in a battery.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon negative electrode material

    CN113363458A

  • Preparation method and energy storage application of silicon carbon / graphene composite material

    CN114906834A

  • Natural graphite-based silicon-carbon composite negative electrode material as well as preparation method and application thereof

    CN111333063A